2020
DOI: 10.1016/j.econmod.2020.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Insolvency regimes and firms' default risk under economic uncertainty and shocks

Abstract: One of the arguments often advanced for implementing a stronger insolvency and bankruptcy framework is that it enhances credit discipline among firms. Using a large crosscountry firm-level dataset, we empirically test whether a stronger insolvency regime reduces firms' likelihood of defaulting on their debt. In particular, we examine whether it reduces default risk during increased economic uncertainty and various external shocks. Our results confirm that a stronger insolvency regime moderates the adverse effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 72 publications
2
16
0
Order By: Relevance
“…The increased usage of digital technologies constantly generates new industrial growth points, providing tremendous force for the long-term development of new energy enterprises (Jabłoński, 2018). Besides, scholars also investigate how the digital economy impacts enterprise business models (Tan et al, 2007), organizational structures (Nuryaman, 2015), governance mechanisms (Gopalakrishnan and Mohapatra, 2020), Etc.…”
Section: Open Access Edited Bymentioning
confidence: 99%
“…The increased usage of digital technologies constantly generates new industrial growth points, providing tremendous force for the long-term development of new energy enterprises (Jabłoński, 2018). Besides, scholars also investigate how the digital economy impacts enterprise business models (Tan et al, 2007), organizational structures (Nuryaman, 2015), governance mechanisms (Gopalakrishnan and Mohapatra, 2020), Etc.…”
Section: Open Access Edited Bymentioning
confidence: 99%
“…Using a large cross-country firm-level dataset, Gopalakrishnan and Mohapatra [31] demonstrated that companies with higher cash flows and higher growth often have higher Z-scores, indicating a lesser propensity to default. Asset tangibility is linked to default risk because businesses with more tangible assets have lower Z-scores.…”
Section: Firm Specific Determinants Of Probability Of Defaultmentioning
confidence: 99%
“…Fama et al [46,47] found that economic conditions significantly affect the probability of default. Gopalakrishnan and Mohapatra [31] found that that firms in countries with higher GDP growth tend to have a lower likelihood of default. Schuermann et al [48] showed that the interrelationship between the condition of the economy and firms is the main driver of defaults.…”
Section: Macroeconomic Factors Affecting Probability Of Defaultmentioning
confidence: 99%
“…The marketing aspects of credit risk management were emphasized by E. Webb & S. Shu (2018), the influence of borrowers' default on the level of credit risk of banking institutions was studied by B. Gopalakrishnan & S. Mohapatra (2020). Estimation of credit risks in agriculture in terms of natural and climatic conditions is rather specific, which was outlined in papers by O.…”
Section: Introductionmentioning
confidence: 99%